Interpretasi Kombinatorial Kongruensi Fungsi Partisi Biner Modulo 2 - Agung Aldhi Prastya; Uha Isnaini (UNIVERSITAS NEGERI PADANG, 2023)
A partition of a positive integer n is a non-increasing sequence of finite positive integers such that the sum is equal to n. One thing that is studied by some researchers in integer partition is binary partition. A binary partition of a positive integer n is a non-increasing sequence of finite positive integers that are powers of 2 and sum to n. The number of binary partitions of n is denoted by b(n) and is called the binary partition function. In this study, we provides a combinatorial interpretation of a congruence of binary partition functions modulo 2. The interpretation involves dividing all binary partitions of n into two sets with the same cardinality using a bijective function that maps binary partitions satisfying certain conditions to binary partitions satisfying other conditions.